CRIMINAL LIABILITY FOR LOOTING UNDER MARTIAL LAW - Lykhova, Sofiia; Polishchuk, Daria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to analyze the application of criminal legislation in relation to such a crime as looting, which is committed under martial law, the interpretation of the concept of looting and certain related military criminal offenses, and the study of the issue of strengthening criminal liability for looting under martial law. Methods: the research was conducted using dialectical and historical approaches, methods of analysis, induction, synthesis, comparative method. Results: conclusions were formed regarding the application of sanctions of the relevant articles, the provisions of which provide for the legal composition of criminal offenses committed under martial law and the application of circumstances that aggravate punishment and qualifying circumstances in the qualification of crimes. Discussion: taking into account the comprehensive analysis of the issue of increasing criminal liability for looting under martial law, the article examines both the composition of the crime «Looting» (Article 432 of the Criminal Code of Ukraine) and the sanction of this article. Having analyzed the expediency of applying aggravating circumstances during qualification, if the crime was committed without using the conditions of martial law, but under the conditions of this regime. The article also examines the legal components of crimes that contain an aggravating circumstance «under martial law» (Articles 185, 186, 187, 189, 191 of the Criminal Code of Ukraine). Considering looting from different angles, it is possible to identify some aspects that more widely interpret this concept through the prism of socially dangerous acts during the course of historical events on the territory of Ukraine during the Second World War. However, the contradictory positions of the majority of scientists and practicing lawyers regarding the qualification of acts committed under martial law as looting remain widespread for the practical application of the legal norm.